"As is" America: Subcontracting freedom. (14th September 2021) - Baptist, Najja K.
Abstract: Objective: This study examines the nature and uses of the Constitution as a social contract. America's original agreement with its Black citizens, under the three—fifths clause of the Constitution, is one of commodification. The Constitution constructs the Black body as expendable property in a subcontract. Police protect and serve in maintaining this status quo. Methods: This research analyzes the literature on the social contract theory. This paper compares classical theorists such as Locke, Rawls, and Nozick with opposing literature from Rousseau, Mills, and Pateman. This comparison highlights what many consider "just" as a thinly veiled attempt to justify the legality of the state's actions. Also, there is a review of Graham v. Oconnor to determine how case law upholds the subjugation of Black bodies as part of the subcontract. Results: My research suggests that Black citizens are only entitled to the rights and privileges of a subcontract. This subcontract allows for the harassment, unequal treatment, and in some instances, the death of marginalized groups by police at any time. Conclusion: From the extrajudicial killing of Amadou Diallo to that of Breonna Taylor, it is evident from the past two decades that Black lives are expendable; police officers continue to enforce the fugitive slave clause, which allows for punishment by death for the assumption of criminal behavior. My research helps illuminate the relationship between the Black experience and police encounters as a proxy of a subcontract within the Constitution. These events—the lawless actions of police officers, and a political and legal system that supports these actions—fuel recent waves of the BLM movement.